Implementation of the information system and observatories of economic and social dynamics for decision making - Quispe Llanos, Renán (2013)
This article deals with the electronic information system that was implemented and put into operation for the FIECS-UNI, in response to the need to have a database that provides statistical, economic and social information for decision making. However, this information is available to teachers, researchers and students of the university.